2004
DOI: 10.1074/jbc.m307859200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Membrane-associated Rhoptry Protein of Plasmodium falciparum

Abstract: Invasive forms of apicomplexan parasites contain secretory organelles called rhoptries that are essential for entry into host cells. We present a detailed characterization of an unusual rhoptry protein of the human malaria parasite Plasmodium falciparum, the rhoptryassociated membrane antigen (RAMA) that appears to have roles in both rhoptry biogenesis and host cell invasion. RAMA is synthesized as a 170-kDa protein in early trophozoites, several hours before rhoptry formation and is transiently localized with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
139
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 57 publications
4
139
0
Order By: Relevance
“…Monoclonal antibodies directed against epitopes within Ag44 showed growth-inhibitory properties in in vitro assays (6,7). As in vitro RBC-binding assays indicated that Ag44 harbors an RBC-binding domain (21), there appears to be a link between protection and responses to RBC-binding domains for both RAMA and RhopH3.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Monoclonal antibodies directed against epitopes within Ag44 showed growth-inhibitory properties in in vitro assays (6,7). As in vitro RBC-binding assays indicated that Ag44 harbors an RBC-binding domain (21), there appears to be a link between protection and responses to RBC-binding domains for both RAMA and RhopH3.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies of the IgG3 isotype directed to fragment E are strongly associated with resistance to infection in our study population. Fragment E contains the RBC-binding domain and may be involved in the process of merozoite entry and the formation of the parasitophorous vacuole (21). As such, RAMA-E might have potential as a candidate for inclusion in an antimalarial vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations